Responsibility Student Budgeting Procedure in Polytechnic Batam - Sinarti Sinarti; Dessy Ratna Sary (Journal of Applied Accounting and Taxation, 2016)
This research is discuss about the procedure for making the grant implementation work programs to attract the use of budgetary procedures of Student Affairs at Polytechnic Batam Student Affairs Organization. The funds badly needed by the student organization to run all programs of work which will be carried out during a period of stewardship. Financing for the activities of the student organization is regulated in the decision of the Minister of education and culture of the Republic of Indonesia No. 155/U/98, on the organization of Student Affairs General Guidelines College and the Statute of the College. All of activity that has been carried out must be made in the report of accountability activities as accountability for the use of the grant implementation of work programs.